2014
DOI: 10.1332/175982714x13971346086512
|View full text |Cite
|
Sign up to set email alerts
|

‘Beat the cheat’: portrayals of disability benefit claimants in print media

Abstract: The Welfare Reform Act (2012) brought about changes to benefit entitlement and assessment for disabled people, with measures to reduce the budget in this area justified within parts of the Conservative Party and right-wing media through the use of narratives of deserving and undeserving citizens. Using a case study of the Sun newspaper's publications on disability in 2012, this paper illustrates that increasingly negative perceptions of disabled people in society are congruent with dominant portrayals of disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Such well‐formed opinions are likely a reflection of the continued ‘moralising’ over the ‘social problem’ of persistent unemployment. The media tends to blame, shame and stigmatize unemployed people and welfare claimants (Taylor‐Gooby ; McEnhill and Byrne ). Citizens who fail to secure paid work are the social differentiated ‘other’ (not‐me) it seems; once again defined as the ‘undeserving poor’ members of British society as Coats () observes.…”
Section: Resultsmentioning
confidence: 99%
“…Such well‐formed opinions are likely a reflection of the continued ‘moralising’ over the ‘social problem’ of persistent unemployment. The media tends to blame, shame and stigmatize unemployed people and welfare claimants (Taylor‐Gooby ; McEnhill and Byrne ). Citizens who fail to secure paid work are the social differentiated ‘other’ (not‐me) it seems; once again defined as the ‘undeserving poor’ members of British society as Coats () observes.…”
Section: Resultsmentioning
confidence: 99%
“…Participants' opinions about welfare and social security affects how they view the stress that arises from needing welfare support themselves. The different sources of welfare stigma [46][47][48] played a role in this, but social stigma was the biggest concern: "Yeah. More to do with that and having self-respect basically.…”
Section: (Participant 17)mentioning
confidence: 99%
“…Heslop and Gordon ([6], p. 209), for example, found that "The experience of deprivation and disadvantage for households with disabled people has considerably worsened over the past 13 years..." This could in part have been the result of welfare reform, with, for instance, Reed and Portes ([7], p. 5) finding that the impacts of tax and welfare reforms have been "more 1negative for families containing at least one disabled person". Further, the nature of welfare reform (e.g., [8]) appears to have entailed misrecognition towards disabled people, with, for example, the disrespect at the heart of government and media benefit cheat narratives (e.g., [9]). In addition, misrecognition and maldistribution can feed into each other.…”
Section: Social Justice and Disabled Individualsmentioning
confidence: 99%
“…First, the welfare discourse is an individualising one (e.g., [84]), in which the role of individual "deficiencies" (such as an impairment) are focussed on as the principal cause of individuals being unemployed, rather than either structural problems (such as insufficient demand in the economy) or employer deficiencies (including not being prepared to make adjustments). In addition, this individualising discourse has increasingly entailed negative government and media narratives about "disability benefit cheats" (e.g., [9]), with Harwood [10] finding that these "narratives could be spilling-over into the work place and encouraging some managers to question the honesty of adjustment requests". There was considerable evidence, from the RAS, that this individualising discourse and "benefit cheats" narrative was reducing organisational focus on the need to make adjustments and providing a pretext in some cases for not making them.…”
Section: Flexible Labour Market Policiesmentioning
confidence: 99%
See 1 more Smart Citation